AJARAN PENGENDALIAN DIRI YOGA TERHADAP PERILAKU FLEXING DI SOSIAL MEDIA - Purnomo, Budi (Fakultas Dharma Duta, 2025)
Technology cannot be separated from the human’s live. Technological advances, especially the use of the internet in life, are a necessity. Social media, as a means of communication and information, is one of the favorites of internet users in Indonesia. Although in its use, it can have negative impacts if not accompanied by good digital literacy. One of the phenomena of social media users that has the potential to have negative impacts is flexing or showing off behavior on social media. In order to overcome the negative impacts caused by flexing behavior, a study of the teachings of Yoga self-control and its internalization of flexing behavior on social media was conducted. The relevance of the teachings of Yoga self-control to flexing behavior refers to the teachings of yama and niyama self-control which are the basic foundations of Yoga ethics. Both teachings emphasize physical and spiritual discipline to achieve true happiness.